2008
DOI: 10.1186/1471-2164-9-524
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of wild type yeast strains unveils important genome diversity

Abstract: Background: Genome variability generates phenotypic heterogeneity and is of relevance for adaptation to environmental change, but the extent of such variability in natural populations is still poorly understood. For example, selected Saccharomyces cerevisiae strains are variable at the ploidy level, have gene amplifications, changes in chromosome copy number, and gross chromosomal rearrangements. This suggests that genome plasticity provides important genetic diversity upon which natural selection mechanisms c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
124
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 82 publications
(82 reference statements)
12
124
1
2
Order By: Relevance
“…Structural variation, although abundant, was limited to the end sections of chromosomes. A similar pattern has been previously observed in microarray-based surveys of genome variation among different S. cerevisiae strains (Winzeler et al 2003;Carreto et al 2008;Schacherer et al 2009), which found that most polymorphisms, including SNPs and CNVs, were more common within 25 kb of the telomeres. In these studies, however, the full extent of the structural variation in these regions could not be revealed because the microarrays used were based on the S288c genome, and regions of high sequence divergence or sequences that were absent in the reference strain could not be examined.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Structural variation, although abundant, was limited to the end sections of chromosomes. A similar pattern has been previously observed in microarray-based surveys of genome variation among different S. cerevisiae strains (Winzeler et al 2003;Carreto et al 2008;Schacherer et al 2009), which found that most polymorphisms, including SNPs and CNVs, were more common within 25 kb of the telomeres. In these studies, however, the full extent of the structural variation in these regions could not be revealed because the microarrays used were based on the S288c genome, and regions of high sequence divergence or sequences that were absent in the reference strain could not be examined.…”
Section: Discussionsupporting
confidence: 60%
“…Microarray-based whole-genome hybridization studies of wild, industrial, and laboratory S. cerevisiae strains (Winzeler et al 2003;Carreto et al 2008;Faddah et al 2009;Schacherer et al 2009) have uncovered a recurrent pattern of copy number variation (CNV) near the ends of chromosomes, suggesting a role for repetitive DNA sequences in structural genome diversification. Despite these valuable insights, two central questions regarding the role of chromosomal rearrangements in genome evolution in S. cerevisiae remain unanswered: First, it is still unclear how these rearrangements contribute to long-term fitness in natural environments; and second, it is not known if they are compatible with the formation of viable meiotic spores that would allow their sexual dissemination between natural S. cerevisiae populations.…”
mentioning
confidence: 99%
“…Subtelomeric regions are more generally recognized as extremely dynamic regions of chromosomes (Mefford and Trask 2002;Prieto et al 2004;Gonzalez-Garcia et al 2006;Carreto et al 2008;Nieves et al 2011). In humans, large complex blocks of duplicated sequences-zones of subtelomeric duplication-typically define the last 50-150 kbp of human chromosomes (Mefford and Trask 2002;Riethman et al 2005).…”
mentioning
confidence: 99%
“…Indeed, copy-number variants (CNVs; sometimes also called 'copy-number polymorphisms' or CNPs) have been shown to be widespread in a variety of organisms, including humans (Sebat et al 2004;Conrad et al 2006;McCarroll et al 2006;Redon et al 2006), mice (Graubert et al 2007;She et al 2008), chimpanzees (Perry et al 2006, rhesus macaques (Lee et al 2008), cows (Liu et al 2010), dogs (Chen et al 2009;Nicholas et al 2009), chickens (Griffin et al 2008), maize (Springer et al 2009), Arabidopsis thaliana (Ossowski et al 2008), fruitflies (Dopman & Hartl 2007;Emerson et al 2008), Caenorhabditis elegans (Maydan et al 2010) and Saccharomyces cerevisiae (Carreto et al 2008). Though it is often harder to experimentally identify and genotype CNVs relative to SNPs and indels, many are big enough to encompass whole genes and are therefore more likely to affect organismal fitness.…”
Section: Introductionmentioning
confidence: 99%